2001
DOI: 10.1055/s-2001-16947
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing breath condensate volume

Abstract: Analysis of breath condensate (BC) has received interest recently due to the need for easy and repetitive monitoring or airway and pulmonary disease. While many authors have used custom built systems, commercial systems are now available and will probably be used more widely. Early studies of markers and mediators in BC have reported concentrations following varying periods of sampling time. However, factors that influence the generation of BC have not been analysed and it is unclear whether breathing rate, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
4

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 9 publications
(10 reference statements)
6
64
1
4
Order By: Relevance
“…This mediator is not age-dependent in children, but higher levels were found in older than younger adults [13,33,34]. Body weight or height do not affect EBC volume and H 2 O 2 concentration in adults [28]; however no data are available regarding other mediators.…”
Section: Age and Sexmentioning
confidence: 91%
See 4 more Smart Citations
“…This mediator is not age-dependent in children, but higher levels were found in older than younger adults [13,33,34]. Body weight or height do not affect EBC volume and H 2 O 2 concentration in adults [28]; however no data are available regarding other mediators.…”
Section: Age and Sexmentioning
confidence: 91%
“…Exhalation flow influences the level of exhaled H 2 O 2 ; at higher flows exhaled H 2 O 2 concentration is lower, but with the low flows during tidal breathing the effect is minor [19]. A strong correlation was found between total respired volume and breath condensate volume by different authors [11,28]. An animal study showed clear positive correlations not only between minute volume and EBC volume, but also to variables determining the breathing pattern (i.e.…”
Section: Breathing Patternmentioning
confidence: 99%
See 3 more Smart Citations